Perilaku Personal Hygiene Terhadap Anak Jalanan di Kota Makassar Tahun 2016 - Jusfaega, Jusfaega; Nurdiyanah, Nurdiyanah; Syarfaini, Syarfaini (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Personal hygiene is an action to maintain the cleanliness of oneself, welfare, physical and psychological to improve health. Street children is identified as a community that lack of attention to healthy behavior. This has resulted in disruption in their daily lives, especially personal hygiene needs. This study aims to determine the behavior of knowledge about personal hygiene, body image, social support, and the availability of street children in the city of Makassar in 2016. The design study is qualitative phenomenological approach. Determination of informants using purposive sampling technique. The collection of data through indepth interviews in the form of a dialogue of individuals using interview guide. The survey results revealed that there was some street children who already know but have not yet fully understood. Street children body image that they believe themselves to clothing that is used everyday, want to look attractive. The role of parents emotionally to street children who support children to always maintain personal hygiene and some parents actually indifferent and the support of volunteers in the information to street children. Besides supporting facilities in implementing good personal hygiene is still zero in a halfway house and save street child at home street children. Interest groups especially to a halfway house in order to provide a more focused attention on the importance of maintaining personal hygiene and provide guidance to street children for creativity that is worth selling as a source of income. Keywords : Personal Hygiene, Save Street Child, Street Children